A Comparative Study of the Interpretation Methods Mohammed Arkoun and Nasr Hamid Abu Zaid from a Hermeneutic Perspective - Ana Syelviana; Amilatul Islamiyah (DAAR EL-KAMIL: Multidisciplinary Journal, 2026)
The debate on the reading of the Qur'an and methods of interpretation represents a dynamic and evolving aspect of academic discourse, particularly within the context of the contemporary intellectual landscape. Two of the most prominent Muslim intellectuals are Mohammed Arkoun and Nasr Hamid Abu Zaid. The two figures in question exhibit similarities in their approach to Qur'anic interpretation, particularly in their reliance on Arabic literary sources. However, they employ disparate methodologies in their respective interpretations of the Qur'an. The objective of this article is to examine the methods proposed by Mohammed Arkoun and Nasr Hamid Abu Zaid and to ascertain how these two figures interpret the contemporary Qur'an. A comparative study revealed that Mohammed Arkoun and Nasr Hamid Abu Zaid adopt a similar approach, namely hermeneutics. However, the hermeneutical approach of each figure differs. Nasr Hamid Abu Zaid adheres to a progressive quasi-objectivist hermeneutical perspective, whereas Mohammed Arkoun espouses a subjectivist hermeneutical stance. In his approach to reading the Qur'an, Arkoun draws upon epistemological principles, whereas Nasr Hamid Abu Zaid employs discourse criticism. Arkoun regards the Qur'an as the language of revelation enshrined in the corpus (the Ottoman Mushaf) as God's parole. In contrast, Nasr Hamid Abu Zaid views the Qur'an as a historical text that must be contextualised in order to gain an accurate understanding of its ideals, which are shālihun likulli zamān wa makān.